The 3 Bs of cancer care amid the COVID‐19 pandemic crisis: "Be safe, be smart, be kind"—A multidisciplinary approach increasing the use of radiation and embracing telemedicine for head and neck cancer. Issue 18 (8th July 2020) - Kang, Jung Julie; Wong, Richard J.; Sherman, Eric J.; Rybkin, Alisa; McBride, Sean M.; Riaz, Nadeem; Tsai, C. Jillian; Yu, Yao; Chen, Linda; Zakeri, Kaveh; Gelblum, Daphna Y.; Gillespie, Erin F.; et al.
Abstract : Because of the national emergency triggered by the coronavirus disease 2019 (COVID‐19) pandemic, government‐mandated public health directives have drastically changed not only social norms but also the practice of oncologic medicine. Timely head and neck cancer (HNC) treatment must be prioritized, even during emergencies. Because severe acute respiratory syndrome coronavirus 2 predominantly resides in the sinonasal/oral/oropharyngeal tracts, nonessential mucosal procedures are restricted, and HNCs are being triaged toward nonsurgical treatments when cures are comparable. Consequently, radiation utilization will likely increase during this pandemic. Even in radiation oncology, standard in‐person and endoscopic evaluations are being restrained to limit exposure risks and preserve personal protective equipment for other frontline workers. The authors have implemented telemedicine and multidisciplinary conferences to continue to offer standard‐of‐care HNC treatments during this uniquely challenging time. Because of the lack of feasibility data on telemedicine for HNC, they report their early experience at a high‐volume cancer center at the domestic epicenter of the COVID‐19 crisis. Abstract : Cancer care is undeniably affected by the coronavirus disease 2019 (COVID‐19) public health emergency, but quality cancer care must persist. A high‐volume cancer center from the domestic epicenter of the COVID‐19 crisis shares its multidisciplinary approach to integrating current public health restrictions and adopting telemedicine to optimize the care of patients with head and neck cancer; it is hoped that this center's experience will provide helpful insights to oncology colleagues.